EFFECT OF ORGANIC ACID SUPPLEMENTATION IN DRINKING WATER ON HEMATOLOGICAL AND BIOCHEMICAL PARAMETERS OF JAPANESE QUAIL - Farqad Shawqi Ibrahim; Ali H Al-obaidy (Indian Journal of Veterinary and Animal Sciences Research, 2026)
This study aimed to evaluate the effects of supplementation of a mixture of acetic acid and citric acid in drinking water on hematological and biochemical parameters in male and female Japanese quails. A total of 540 day-old quails were randomly distributed into four treatments and three replicates with 135 birds for each group as follows: T1 drinking water without acids; T2, T3, and T4 treatments with 1ml+1g, 2ml+2g, and  3ml+3g of acetic acid + citric acid per liter of drinking water, respectively. At 42 days of age, blood samples were collected from six quails per treatments (three repicats per sex)for haematological and biochemical analysis. The results showed that the organic acid mixture significantly (P≤0.01)  increased red blood cell count, packed cell volume, haemoglobin concentration, and high-density lipoprotein levels in both males and females. It also significantly decreased cholesterol, triglyceride, low-density lipoprotein, and  aspartate  aminotransferase  levels  in  both  sexes.  Significant increase  in  total protein(P≤0.05)  and globulin (P≤0.01) levels in males, while albumin levels increased significantly (P≤0.01) in females was also observed. In conclusion, adding acetic and citric acids to drinking water positively influenced haematological and biochemical parameters, indicating enhanced health and productive performance in Japanese quails.